(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, in the biographical, sociological, analytical and comparative-typological aspect, the factors of the emergence and development of the epic, the ways of manifestation of historical reality and the concept of personality in Uzbek and world novels - epics are studied.